EFFECT OF MACROPRUDENTIAL POLICY INSTRUMENTS ON CREDIT GROWTH FOR COMMERCIAL BANKS IN INDONESIA - Aslamah, Afidah Nur; Pratama, Aditya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
The Indonesian economy experienced a deep contraction in 2020 due to the COVID-19 pandemic. The economic growth rate took a sharp dip at -5.32% in the first quarter based on data from BPS. One of the impacts is the decline in credit growth in the banking sector, which grew only 0.12% per August. The government is trying to control the rate of credit growth by introducing policies in the monetary sector, namely a change in the statutory reserve requirement (GWM) from 8% to 4% in order to maintain banking liquidity. The purpose of this study was to analyze the effect of the statutory reserve requirement, Macroprudential Intermediation Ratio (MIR), and capital buffer on the growth of commercial bank credit in Indonesia 2019-2020. The data used is monthly data from the Indonesian Banking Statistics on the website of the Financial Services Authority. The statistical method used in this study is the multiple linear regression method with E-Views SV.11 software to perform the three hypothesis tests. The results of the study partially show that the reserve requirement has a negative and insignificant effect on commercial bank credit growth. MIR and capital buffer have a significant effect, but MIR has a negative effect and capital buffer has a positive influence on commercial bank credit growth.